A nonlinear seepage model of gas and water transport in multi-scale shale gas reservoirs based on dynamic permeability. (18th April 2018) - Huang, Ting; Li, Erpeng; Tao, Zhengwu; Guo, Xiao
Abstract: Flow in extremely low permeability shale gas reservoirs undergoes a transition from a Darcy regime to other flow regimes including slip flow, transition flow and free molecular flow, due to the significant effect of molecular collisions with pore walls on gas transport. These various flow regimes in shales and their effect on actual gas production are not clearly understood, and multi-fractured horizontal wells are crucial for the economic production of unconventional resources. Therefore, a numerical model which is valid for the entire Knudsen range (continuum flow, slip flow, transition flow and free molecular flow) in shale gas reservoirs has been developed, with the effect of gas–water flow and the simulation of hydraulic fracturing cracks taken into consideration as well. Furthermore, the effect of different flow regimes on both the dynamic permeability of shales and then the actual gas production rate are analyzed thoroughly, and we study the influencing factors such as gas–water flow and fracturing treatment. The simulation results of the developed model are validated with other numerical models and field data. It is concluded that different flow regimes, considering slippage and diffusion in nanopores, have a greater impact on gas production when shale permeability is lower than 1 × 10 −4 mD. The presented numerical model can provide a theoretical basis for evaluating and predicting the productivity of shale gas wells.